2002
DOI: 10.1021/jf025727g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of o,p-EDDHA and Its Detection as the Main Impurity in o,o-EDDHA Commercial Iron Chelates

Abstract: Ethylenediamine-N,N'bis(o-hydroxyphenyl)acetic acid (o,o-EDDHA) is one of the most efficient iron chelates employed to relieve iron chlorosis in plants. However, the presence of positional isomers of EDDHA in commercial iron chelates has been recently demonstrated, and among them, it has been claimed that ethylenediamine-N(o-hydroxyphenylacetic)-N'(p-hydroxyphenylacetic) acid (o,p-EDDHA) is the main impurity present in EDDHA fertilizers. Here we report the preparation of o,p-EDDHA, a compound whose synthesis h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 20 publications
3
36
1
Order By: Relevance
“…In the present work this process was studied and it could be observed that o,p-EDDHA was the fastest chelating agent solubilising Fe from several Fecontaining minerals and selected soils. This fact can be due to the coordination of the Fe 3+ inside the chelate; this chelating agent has five donor groups able to bind Fe instead of six and thus it could yield a faster solubilisation of Fe (Go´mez-Gallego et al, 2002). Nevertheless, the maximum amount of Fe that can be solubilised was high for o,o-EDDHA and low for EDTA.…”
Section: Fe Solubilisation From Soils and Fe Oxidesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present work this process was studied and it could be observed that o,p-EDDHA was the fastest chelating agent solubilising Fe from several Fecontaining minerals and selected soils. This fact can be due to the coordination of the Fe 3+ inside the chelate; this chelating agent has five donor groups able to bind Fe instead of six and thus it could yield a faster solubilisation of Fe (Go´mez-Gallego et al, 2002). Nevertheless, the maximum amount of Fe that can be solubilised was high for o,o-EDDHA and low for EDTA.…”
Section: Fe Solubilisation From Soils and Fe Oxidesmentioning
confidence: 99%
“…However, due to its lower stability constant, o,p-EDDHA/ Fe 3+ is expected to disappear sooner than o,o-EDDHA/Fe 3+ from alkaline soil solutions. This behaviour may be related to the presence of only five bonds between the Fe and the ligand (Go´mez-Gallego et al, 2002). Thus, while o,p-EDDHA/Fe 3+ can be a good chelate to correct Fe chlorosis, it is likely to be active for only a short time due to its low stability in soils .…”
Section: Fe Solubilisation From Soils and Fe Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…EDDHA is industrially prepared by a Mannich-like reaction between phenol, ethylenediamine and glyoxylic acid (Petree et al 1978). This pathway is known to produce around 4-6% Fe chelated with o,o-EDDHA as the main component, together with a mixture of positional isomers that have been identified as o,p-EDDHA and p,p-EDDHA (Cremonini et al 2001;Gómez -Gallego et al 2002) accompanied by other unknown by-products that are also able to complex Fe 3+ . The o, oEDDHA positional isomer is found to form the most stable complexes with iron (Hernández- Apaolaza et al 1997;Yunta et al 2003a) and presents two regioisomers (meso and racemic) with different agronomic efficacy (Cerdán et al 2006); o,pEDDHA has now been included as an authorized chelating agent in the European Regulation on fertilizers (EC Regulation No.…”
Section: Introductionmentioning
confidence: 99%
“…A novel method using cyanide transfer agents instead of HCN has been developed, although it has not yet been scaled up for industrial applications 16. Current industrial synthesis processes17, 18 lead to products which often contain starting chemicals as well as reaction byproducts 15, 19–26. For this reason, a common characteristic of these fertilizers is the occurrence of a significant water‐soluble Fe fraction not bound to the authorized chelating agents 20–22.…”
mentioning
confidence: 99%